2019
DOI: 10.1177/0046958019838367
|View full text |Cite
|
Sign up to set email alerts
|

Limited Consequences of a Transition From Activity-Based Financing to Budgeting: Four Reasons Why According to Swedish Hospital Managers

Abstract: Activity-based financing (ABF) and global budgeting are two common reimbursement models in hospital care that embody different incentives for cost containment and quality. The purpose of this study was to explore and describe perceptions from the provider perspective about how and why replacing variable ABF by global budgets affects daily operations and provided services. The study setting is a large Swedish county council that went from traditional budgeting to an ABF system and then back again in the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…From a regulative perspective it was evident that not everyone was informed about the regulative changes, since information was “buffered” through management. This has previously been shown to affect whether healthcare providers adapt to regulative changes ( Ellegard and Glenngard, 2019 ). Further, it was also clear that management had other demands to take into account, which was evident when quality aspects of physiotherapy were neglected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a regulative perspective it was evident that not everyone was informed about the regulative changes, since information was “buffered” through management. This has previously been shown to affect whether healthcare providers adapt to regulative changes ( Ellegard and Glenngard, 2019 ). Further, it was also clear that management had other demands to take into account, which was evident when quality aspects of physiotherapy were neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing understanding requires leadership skills such as communication with, and motivation of, involved staff ( Nilsson and Sandoff, 2015 ). It is also important to acknowledge the importance of managers who can dampen and modify external demands ( Ellegard and Glenngard, 2019 ). Further, our study showed that professional groups that lacked representation in the design of the programme, considered that as a problem, since each professional category can contribute with different perspectives in the care chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for a policy reformation to be successful, these different logics need to be taken into account. It is also important to acknowledge the importance of managers, who can dampen and modify external demands (Ellegard & Glenngard, 2019).Some of the spine surgery clinics used interdisciplinary teams to assess patients before the VBRP was introduced. After the introduction, several clinics said that they were looking for similar solutions.…”
Section: +Sheds Light On the Importance Of Other Perspectives When Treating A Patientmentioning
confidence: 99%
“…From a regulative perspective it was evident that not everyone was informed about the regulative changes, since information was "buffered" through management. This has previously been shown to affect whether healthcare providers adapt to regulative changes (Ellegard & Glenngard, 2019). Furthermore, it was also clear that management had other demands to take into account, which was evident when quality aspects of physiotherapy were neglected.…”
Section: Pitfallsmentioning
confidence: 99%